DEFORMATION PATTERN OF THE PALAEOZOIC UNITS OF THE TETHYAN SUTURE IN THE CENTRAL BALKAN PENINSULA: A NEW INSIGHT FROM STUDY OF THE BUKULJA-LAZAREVAC PALAEOZOIC UNIT (SERBIA) - Trivić, Branislav; Cvetković, Vladica; Smiljanić, Biljana; Gajić, Rodoljub (Ofioliti, 2010)
This study presents and discusses new data about the lithology and deformation style of the Bukulja-Lazarevac Palaeozoic Unit (BLPz) and compares its characteristics to those exhibited by the adjacent Palaeozoic units of the complex suture of the central Balkan Peninsula, namely: the Drina-Ivanjica (DIU), the Jadar Block (JBU) and the Diãina Palaeozoic (DPz) Units. The BLPz consists of four metasedimentary and metaigneous formations metamorphosed under greenschist facies conditions. Only rare rocks show evidences of an earlier metamorphism of amphibolites facies conditions. The BLPz is lithologically similar to DIU and DPz whereas JBU is different. The study of deformation suggests that BLPz rocks underwent two ductile tectonic events, referred to as D1 and D2, and one brittle event, referred to as D3. The D1 structures are small-scale isoclinal and oblique folds with subrounded hinges and statistical B1 axes dipping around 5-20o towards E-ESE and SE. The D2 structures appear as m- to dm-sized folds formed on the limbs of the larger fold structures. Statistically, B2 axes are mainly dipping to SE, subordinately to NW and SW. The angle between B1 and B2 axes is uniform ranging from 35o to 45o. Evidences for two similar deformation events are recorded in DIU, JBU and DPz, as well. Reconstruction of the original position of B1 axes was made by rotating their measured directions around the statistic directions of B2 fold axes. The obtained results imply that the B1 axes in the northern part of DIU (Drina Block) and JBU have the same primary orientation striking NE-SW. The southern part of DIU (Ivanjica Block) and BLPz Units are characterized by E-W oriented B1 structures. Such organization suggests that all the studied Palaeozoic units probably underwent similar events of ductile deformation. These results argue in favor of the hypothesis that these units represented integral parts of Adria, and obtained their present relationships during post-Jurassic nappe stacking.